Straw burning Issues and prevention strategies - Nikam, Vinayak; Singh, Dharminder (Indian Farming, 2020)
The region which was praised for bringing green revolution to India and making country selfsufficient in food grains is in news every winter. However, it is not for good reason but as a cause of severe blanket of fog over Delhi and NCR region starting from the month of November. Though this smoke is also affecting the health of farmers, women and children in villages; soil health loss etc., farmers are compelled to burn stubbles because of short window available between harvesting of rice and sowing of next crop i.e. wheat. Though many measures have suggested to curb the problem but adoption of alternatives is limited. Therefore, situation demands that the solution to this problem are economically viable, culturally accepted by farmers and driven by them.